Hubungan Tingkat Stress dan Kualitas Tidur pada Mahasiswa Fakultas Kedokteran Tahap Akademik Universitas Islam Bandung - Rayna Farizkia Dinda; Arief Budi Yulianti; Uci Ary Lantika (Bandung Conference Series: Medical Science, 2023)
Abstract. Medical students undergo a difficult and stressful period of education. Not infrequently stress becomes a problem that is often experienced by medical students. Stess can trigger sleep disorders. The source of student stress is caused by several factors such as complicated academic requirements, the many types of exams faced, the frequency of frequent assignments and exams, a competitive environment and a busy lecture schedule. Medical students who experience prolonged stress can interfere with student academic achievement. The purpose of this study is to explain the relationship between stress levels and sleep quality of students of the Faculty of Medicine, Islamic University of Bandung with a cross sectional study. The sample in this study was 86 students from the Faculty of Medicine, Bandung Islamic University which was divided into three batches. Sampling is carried out by using probability stratified random sampling techniques. The data collection technique is carried out with a questionnaire in the form of a google form. This study showed that there was a relationship between stress levels and student sleep quality with a p-0.005 score. Most of the medical students of Universitas Islam Bandung are in the category of moderate stress level. Abstrak. Mahasiswa kedokteran menjalani masa pendidikan yang sulit dan penuh dengan tekanan. Tidak jarang stress menjadi masalah yang sering dialami oleh mahasiswa kedokteran. Stess dapat memicu gangguan tidur. Sumber stress mahasiswa disebabkan oleh beberapa faktor seperti persyaratan akademik yang rumit, banyaknya jenis ujian yang dihadapi, frekuensi tugas dan ujian yang sering, lingkungan yang kompetitif dan jadwal perkuliahan yang padat. Mahasiswa kedokteran yang mengalami stress berkepanjangan dapat menggangu pencapaian akademik mahasiswa. Tujuan dari penelitian ini adalah untuk menjelaskan hubungan antara tingkat stress dan kualitas tidur mahasiswa Fakultas Kedokteran Universitas Islam Bandung dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 86 orang mahasiswa Fakultas Kedokteran Universitas Islam Bandung yang terbagi dalam tiga angkatan. Pengambilan sampel dilakukan dengan dengan menggutakan teknik probability stratified random sampling. Teknik pengumpulan data dilakukan dengan kuesioner dalam bentuk google form. Penelitian ini menunjukkan bahwa terdapat hubungan tingkat stress dengan kualitas tidur mahasiswa dengan nilai p-0,005. Sebagian besar mahasiswa kedokteran Universitas Islam Bandung berada di kategori tingkat stress sedang (moderate).